Fractal Rate of Adsorption and Surface Diffusivity of Carbon Dioxide across Mesoporous Adsorbents - M.R. Othman; Martunus; W.J.N. Fernando; J. Kim (Adsorption Science & Technology)
The disordered nature of pore structures in adsorbents suggests the existence of a fractal structure formed by the pores. In this study, fractal theory has been employed to construct a rate and surface diffusivity model for these mesoporous adsorbents. The fractal dimensions for the adsorbent pore were obtained via the Dubinin–Astakhov equation and the Jaroniec equation. The model indicates the existence of three simultaneous gas-flow mechanisms. When the Reynolds number is less than 30, laminar flow is dominant; when the Reynolds number is greater than 1800, turbulent flow is dominant; and when the Reynolds number is in the range 30–1800, a transient region co-exists. Contact experiments employing CO 2 gas with mesoporous hydrotalcite adsorbents were conducted to validate the model. The calculated adsorption of CO 2 from convective models was significantly higher in the turbulent regime. The adsorption rate increased with increasing values of ΔT (T sat – T). The surface diffusivity also increased as ΔT increased, regardless of the flow regime.